Seeing a Blush on the Visible and Invisible Spectrum: A Functional Thermal Infrared Imaging Study - Ioannou, Stephanos; Morris, Paul H.; Baker, Marc; Reddy, Vasudevi; Gallese, Vittorio (Frontiers in Human Neuroscience, 2017)
So far blushing has been examined in the context of a negative rather than a positive reinforcement where visual displays of a blush were based on subjective measures. The current study used infrared imaging to measure thermal patterns of the face while with the use of a video camera quantified on the visible spectrum alterations in skin color related to a compliment. To elicit a blush a three-phase dialogue was adopted ending or starting with a compliment on a female sample (N = 22). When the dialogue ended with a compliment results showed a linear increase in temperature for the cheek, and forehead whereas for the peri-orbital region a linear decrease was observed. The compliment phase marked the highest temperature on the chin independent of whether or not the experiment started with a compliment contrary to other facial regions, which did not show a significant change when the experiment started with a compliment. Analyses on the visible spectrum showed that skin pigmentation was getting deep red in the compliment condition compared to the serious and social dialogue conditions for both the forehead and the cheeks. No significant association was observed between temperature values and erythrocyte displays on the forehead and cheek. Heat is the physiological product of an arousing social scenario however preconceived notions about blushing propensity seem to drive erythrocyte display and not necessarily conscious awareness of somatic sensations.